Pressure effect on micellization of non-ionic surfactant Triton X-100 - Espinosa Silva, Yanis Ricardo (2018)
Micellar aggregates can be arranged in new types of conformational assemblies when they are isotropically compressed. Thus, the pressure effects in the underlying fundamental interactions leading to self-assembly of micellar aggregates can be represented by changes in the phase boundaries with increasing pressure. In this paper, we have employed molecular dynamics simulations to study the self-assembly of micelles composed of the non-ionic surfactant Triton X-100 at the atomic scale, monitoring the changes in the solvation dynamics when the micelles are subjected to a wide range of hydrostatic pressures. The computational molecular model was capable of self-assembling and forming a non-ionic micelle, which subsequently was coupled to a high-pressure barostat producing a geometric transition of the micelle due to changes in the solvation dynamics. Accordingly, under a high pressure regime, the hydrogen bonds are redistributed, the water density is modified, and water acts as an unstructured liquid, capable of penetrating into the micelle.